Water susceptibility and mechanical properties of thermoplastic starch-pectin blends reactively extruded with edible citric acid - Da Roz, Alessandra Luzia; Veiga-Santos, Pricila [UNESP]; Ferreira, Adriane Medeiros; Antunes, Thais Cristina Ribeiro; De Lima Leite, Fabio; Yamaji, Fabio Minoru; De Carvalho, Antonio Jose Felix (FapUNIFESP (SciELO), 2016)
Pectin and starch are edible, non-toxic, biodegradable and obtained from renewable sources. Also have the benefit to be easily cross-linked producing hydrogels. Reactive extrusion with edible citric acid and cross linking interactions was evaluated on extruded thermoplastic in natura and cationic starch-pectin blends. Materials water susceptibility and mechanical properties were characterised. Reactive extrusion decreased (up to 75% in natura starch) mechanical properties. Also have decreased (up to 32.4%) both starch polymers water absorption, indicating the possibility of increasing materials water barrier properties but had the opposite effect on the pectin-TPS material, probably related to a cationic-anionic cross linking, resulting in a hydrogel polymer. Reactive extrusion also have negatively affected mechanical properties of both starch polymers, however increased pectin-TPS blends stress and strain at rupture.
Keywords: Bio-based products; Biodegradable packaging; Extrusion; Pectin; Starch